Comunicação e ética : duplo emprego na imprensa do Rio Grande do Sul - Elmi, Alexandre Claser (2014)
The Dual Employment is a phenomenon that subsists in the Brazilian market of professional Journalism and can be observed from an ethical perspective. It refers to the occasions in which a journalist amasses two working ties related to the Media: one of them in the specific tasks around producing news in newsrooms; the other one in the propagation of information or managing strategies of communication in press offices or organizational communication structures. In Europe and the US there are professional codes of ethics that prohibit double duties or the accumulation of secondary jobs. However, the most important code of conduct of the Press in Brazil, the Brazilian Journalists Code of Ethics, updated in 2007, admits its practice, even if with limitations. In the Brazilian case, the search for a secondary job derives from an economic reality of low wages and the precariousness of the Profession. This dissertation analyzes, using John Thompson s Depth Hermeneutics (DH), the work of journalists with Dual Employment. The objects of study selected were Jornal do Comércio and Correio do Povo newspapers, published in Rio Grande do Sul, for both organizations authorize the practice of accumulating working ties. As of DH, using the Ideological Strategies, also formulated by Thompson, as a research technique texts produced by the selected journalists are interpreted as expressions of a professional culture that tolerates dual activity. This study, based on organizational theories of Journalism, also outlines the importance of professional norms and codes of conduct to regulate the activities and the journalist s individual decisions. The permissiveness regarding the dual function contrasts with the ethical requirements of the journalistic activity's modernization. The question intended to be explored is whether the simultaneous exercise of information assignments that are potentially conflicting endangers two principles of the ethical responsible practice, Autonomy and Transparency, such as presented by Patrick Lee Plaisance.